Antibacterial prophylaxis with ciprofloxacin for patients with multiple myeloma and lymphoma undergoing autologous haematopoietic cell transplantation: a quasi-experimental single-centre before-after study. (July 2018) - Yeshurun, M.; Vaxman, I.; Shargian, L.; Yahav, D.; Bishara, J.; Pasvolsky, O.; Wolach, O.; Lahav, M.; Gurion, R.; Magen, H.; Vidal, L.; Herscovici, C.; et al.
Abstract: Objectives: We aimed to study whether ciprofloxacin prophylaxis reduces infectious complications in patients undergoing autologous haematopoietic cell transplantation (AHCT). Methods: This is a quasi-experimental, retrospective, before-after study. We compared the incidence of bacterial-related complications among 356 patients with multiple myeloma (MM) ( n  = 202) and lymphoma ( n  = 154) who underwent AHCT with ( n  = 177) or without ( n  = 179) ciprofloxacin prophylaxis between 03/2007 and 10/2012 and between 10/2012 and 07/2016, respectively, at a single centre. Results: Febrile neutropaenia, bacteraemia, and pneumonia were significantly more common among patients who underwent AHCT during the second study period and did not receive antibacterial prophylaxis compared with patients who underwent AHCT during the first study period and received antibacterial prophylaxis (89.9% (161/179) vs. 83.1% (147/177), difference 6.9%, 95% CI 0-14.1%, P = 0.002; 15.1% (27/179) vs. 4.5% (8/177), difference 10.6%, 95% CI 4.4-16.9%, p < 0.0001; 12.3% (22/179) vs. 6.2% (11/177), difference 6.1%, 95% CI 0-12.3%, p = 0.04, respectively). The number-needed-to-treat to prevent one episode of bacteraemia, pneumonia, and febrile neutropaenia was 8.6, 8.5, and 13.7, respectively. Patients with ciprofloxacin prophylaxis had higher rates of ciprofloxacin-resistant bacteraemia (62.5% (5/8) vs. 18.5% (5/27), difference 44%, 95% CI 7-70%, p = 0.01). In multivariate analysis, ciprofloxacin prophylaxis significantly decreased the odds of bacteraemia (OR 0.19, 95% CI 0.07-0.52; p < 0.0001) and pneumonia (OR 0.37, 95% CI 0.16-0.85, p = 0.02). Conclusion: According to our single-centre experience, patients with MM and lymphoma undergoing AHCT may benefit from antibacterial prophylaxis with ciprofloxacin.